Nove najdbe steklokrilcev (Lepidoptera: Sesiidae) v Sloveniji - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2002)
The result of the latest research on clearwing moths in Slovenia are four new species for the country: Pennisetia bohemica Králíček & Povolný, 1974, Chamaesphecia schmidtiiformis (Freyer, 1836), Chamaesphecia aerifrons (Zeller,1847) and Chamaesphecia hungarica (Tomala, 1901). Included are also data on a little known species Synanthedon flaviventris (Staudinger, 1883), which is mentioned for our fauna frequently in literature, but without exact data and is not included in the List of Slovenian macrolepidoptera.
Keywords: favna; Lepidoptera; nove vrste; Slovenia; Slovenija; steklokrilci